Correction to: Jayakumar, K., & Sankaran, K. K. (2019). Discrete Linnik Weibull distribution. Communications in Statistics-Simulation and Computation, 48 (10): 3092-117 (Communications in statistics. Simulation and computation, 2024)
In the article "Discrete Linnik Weibull distribution", the authors used the method of maximum likelihood to estimate the unknown parameters of the distribution. They made some mistakes in the estimation procedure and section 7. We present the corrections.